The Swahili Language in the Context of the Geopolitics of Languages on the African Continent (Global Journal of Human-Social Science, 2025)
One of the most outstanding characteristics of the African continent is its multilingual nature. It is estimated that around 2,000 languages are spoken across the African continent, many of which are highly dissimilar from one another. This vast linguistic diversity gives rise to a wide range of cultural identities among the social groups who speak them, while also contributing to numerous power rivalries across different territories. In Africa, both colonial and indigenous languages can be identified, creating a geopolitical dynamic in which colonial languages often prevail, despite efforts to reaffirm native ones. When discussing the geopolitics of language, it is essential to consider both the human groups that speak specific languages and the territories they inhabit. Among the indigenous languages showing significant signs of reaffirmation, Swahili stands out. It has undergone a steady process of diffusion, not only throughout the African continent, but also into countries on other continents.